Kindness and Gentleness - Fadl Al-Ilaahi, author 545232; Preston, Tarik, translator 545233 (Walthamstow : Invitation To Islam, 2003)
The correct meaning of *kindness and gentleness’ in as much as the intended meaning is not to be over compromising in such a way that if he were to meet an open sinner, he makes friends with him and pretends to be pleased with him while never disapproving of his behavior. Nor does it mean that he should be hypocritical or phony. Nor does it mean that he should leave off certain matters of religion. Rather, the intended meaning is having a likable character and personality which means being kind and gentle to the ignorant one while teaching him, and with the sinner when prohibiting him from his sin, and leaving off being harsh with him, and expressing disapproval with kind speech and behavior.